2020
DOI: 10.3389/fphys.2020.00994
|View full text |Cite
|
Sign up to set email alerts
|

Livedo Racemosa – The Pathophysiology of Decompression-Associated Cutis Marmorata and Right/Left Shunt

Abstract: Decompression sickness and arterial gas embolism, collectively known as decompression illness (DCI), are serious medical conditions that can result from compressed gas diving. DCI can present with a wide range of physiologic and neurologic symptoms. In diving medicine, skin manifestations are usually described in general as cutis marmorata (CM). Mainly in the Anglo-American literature the terms cutis marmorata, livedo reticularis (LR), and livedo racemosa (LRC) are used interchangeably but actually describe pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…5 A retrospective case-control study showed that 18 divers who had livedo racemosa in the context of an undeserved DCS all had a right/left shunt, 83% of which was an intracardiac shunt. 6 Moreover, PFO closure is associated with a decrease in DCS. 7 Though our medical center does not propose PFO closure for recreational diving, international consensus recommends, in patients who experimented DCS related to a PFO, either to cease diving, to dive more conservatively to reduce the risk of DCS, or to close the PFO.…”
Section: Discussionmentioning
confidence: 99%
“…5 A retrospective case-control study showed that 18 divers who had livedo racemosa in the context of an undeserved DCS all had a right/left shunt, 83% of which was an intracardiac shunt. 6 Moreover, PFO closure is associated with a decrease in DCS. 7 Though our medical center does not propose PFO closure for recreational diving, international consensus recommends, in patients who experimented DCS related to a PFO, either to cease diving, to dive more conservatively to reduce the risk of DCS, or to close the PFO.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it has a pathognomonic role when it appears after diving. 15 Several risk factors have been associated with the development of DCI. Males are considered more prone than females.…”
Section: Decompression Sicknessmentioning
confidence: 99%
“…In addition to these factors, the report also indicates the existence of an IEDCS relationship with persistent oval foramen (PFO), a type of right-to-left shunt (RLS) (Hartig et al, 2020;Mitchell & Doolette, 2015). RLS allows blood to pass through the pulmonary system.…”
Section: Pathophysiologymentioning
confidence: 99%
“…RLS allows blood to pass through the pulmonary system. In other words, the gas bubbles that form in the venous circulation are not excreted by the lungs and can enter the arterial circulation or rather referred to as arterial gas embolism (AGE) (Gempp & Louge, 2013a;Hartig et al, 2020). One study found in 77% of IEDCS cases, large RLS was detected with greater right-side lateralization (80%).…”
Section: Pathophysiologymentioning
confidence: 99%